Direct shoot organogenesis and plant regeneration from hypocotyl explants in selected genotypes of Leucaena leucocephala - a leguminous pulpwood tree - Sirisha, V. L.; Prashant, S.; Ranadheer, D.; Ramprasad, P.; Shaik, N. M.; Arha, Manish; Gupta, S. K.; Srivastava, Sarneer; Yadav, A. K.; Kulkarni, P. S.; Othalathara U. Abhilash; Khan, Bashir Mohammad; et al. (Indian Journal of Biotechnology, 2008)
An efficient in vitro plant regeneration system in subabul (Leucaena leucocephala), a leguminous pulp wood tree species, was established. The induction of shoots was achieved from selected elite clones of subabul K-8, K-636 and also wild type on MS medium supplemented with 2% sucrose and different concentrations (0.88 to 24.6 mu M) of plant growth regulators (BA, Kn, 2iP & TDZ). The best medium for shoot regeneration was MS with 22.2 mu M BA (5 shoots per explant), followed by 22.7 mu M TDZ (4.6 shoots per explant). Addition of putriscine (9.3 mu M) to MS medium containing 22.2 mu M BA enhanced the number of multiple shoots to 7-8 but not the frequency of response. Shoot initials (measuring 1 cm) when separated and transferred on to MS medium containing 1.4 mu M GA(3) elongated to 2-5 cm in 15.20 d with 80% frequency. The per cent frequency of shoot differentiation was almost identical in the genotypes K-8 and K-636 but it differed significantly from the wild type. Leaf yellowing and abscission in all the genotypes was curtailed by supplementing the medium with 685 mu M glutamine or 540 mu M adenine. The excised shoots were transferred to root regeneration media containing 2.46 and 4.98 mu M IBA or 2.6 and 5.3 mu M NAA. Root regeneration was noticed with 100% frequency in all the three genotypes in presence of IBA or NAA. Plantlets were transferred successfully to the pots with 70% survival rate with no visible morphological variations. The protocol can be utilized for mass propagation and genetic transformation studies of this important pulpwood species.
Keywords: hypocotyl explants; Leucaena lucocephala; pulpwood leguminous tree; shoot organogenesis

Phylogenetic analysis, homology modelling, molecular dynamics and docking studies of caffeoyl-CoA-O- methyl transferase (CCoAOMT 1 and 2) isoforms isolated from subabul (Leucaena leucocephala) - Pagadala, Nataraj Sekhar; Arha, Manish; Reddy, P. S.; Kumar, Ranadheer; Sirisha, V. L.; Prashant, S.; Reddy, K. Janardhan; Khan, Bashir Mohammad; Rawal, S. K.; Kishor, P. B. Kavi (Journal of Molecular Modeling, 2009)
Caffeoyl coenzyme A O-methyltransferase (CCoAOMT) is an important enzyme that participates in lignin biosynthesis especially in the formation of cell wall ferulic esters of plants. It plays a pivotal role in the methylation of the 3-hydroxyl group of caffeoyl CoA. Two cDNA clones that code CCoAOMT were isolated earlier from subabul and in the present study; 3D models of CCoAOMT1 and CCoAOMT2 enzymes were built using the MODELLER7v7 software to find out the substrate binding sites. These two proteins differed only in two amino acids and may have little or no functional redundancy. Refined models of the proteins were obtained after energy minimization and molecular dynamics in a solvated water layer. The models were further assessed by PROCHECK, WHATCHECK, Verify_3D and ERRAT programs and the results indicated that these models are reliable for further active site and docking analysis. The refined models showed that the two proteins have 9 and 10 alpha-helices, 6 and 7 beta-sheets respectively. The models were used for docking the substrates CoA, SAM, SAH, caffeoyl CoA, feruloyl CoA, 5-hydroxy feruloyl CoA and sinapyl CoA which showed that CoA and caffeoyl CoA are binding with high affinity with the enzymes in the presence and absence of SAM. It appears therefore that caffeoyl CoA is the substrate for both the isoenzymes. The results also indicated that CoA and caffeoyl CoA are binding with higher affinity to CCoAOMT2 than CCoAOMT1. Therefore, CCoAOMT2 conformation is thought to be the active form that exists in subabul. Docking studies indicated that conserved active site residues Met58, Thr60, Val63, Glu82, Gly84, Ser90, Asp160, Asp162, Thr169, Asn191 and Arg203 in CCoAOMT1 and CCoAOMT2 enzymes create the positive charge to balance the negatively charged caffeoyl CoA and play an important role in maintaining a functional conformation and are directly involved in donor-substrate binding.
Keywords: Caffeoyl-CoA 3-O-methyl transferase; docking; Modelling; S-adenosyl homocysteine

Cloning, characterization and impact of up- and down-regulating subabul cinnamyl alcohol dehydrogenase (CAD) gene on plant growth and lignin profiles in transgenic tobacco - Sirisha, V. L.; Prashant, S.; Kumar, D. Ranadheer; Pramod, S.; Jalaja, N.; Kumari, P. Hima; Rao, P. Maheshwari; Rao, S. Nageswara; Mishra, Preeti; Karumanchi, S. Rao; Khan, Bashir Mohammad; Kishor, P. B. Kavi (Plant Growth Regulation, 2012)
Both cDNA including 5'UTR and 3'UTR and genomic clones of cinnamyl alcohol dehydrogenase (CAD) were isolated and characterized from a pulp-yielding leguminous tree Leucaena leucocephala (LlCAD1). The deduced amino acid sequence shared high identity with orthologous sequences of Acacia mangium x Acacia auriculiformis (83%), Medicago sativa (83%), Nicotiana tabaccum (83%) and Aralia cordata (81%). Full length cDNA contained 78 bases of 5'UTR and 283 bases of 3'UTR, while the genomic clone contained 5 exons and 4 introns. Western blot analysis revealed elevated expression of LlCAD1 in seedling roots and shoots compared to leaves. Sense and antisense CAD tobacco transgenics showed increased and reduced CAD activity accompanied by a change in monomeric lignin composition. Histochemical staining of lignin in down-regulated plants suggested an increase in aldehyde units and a decrease in S/G ratio. Down-regulation of CAD resulted in accumulation of syringic, ferulic, p-coumaric and sinapic acids compared to untransformed controls. These observations were validated by anatomical studies of down-regulated transgenic stems which showed thin walled, elongated phloem and xylem fibres, accompanied by a reduction in the density of vessel elements and amount of secondary xylem when compared to untransformed plants. Furthermore, Klason lignin analysis of CAD antisense transgenics showed 7-32% reduced lignin and normal phenotype as compared to untransformed plants. Such a reduction was not noticed in up-regulated transgenics. These results demonstrate a unique opportunity to explore the significant role that down-regulation of CAD gene plays in reducing lignin content thereby offering potential benefits to the pulp and paper industry.
Keywords: Cinnamyl alcohol dehydrogenase; Lignin down-regulation; Subabul (Leucaena leucocephala); Tobacco